Sensitivitas rapid test untuk mendeteksi hepatitis surface antigen (HBsAg) pada penderita hepatitis-B - Suwarso, Suwarso (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
A new rapid-test, sandwich immunochromatography assay technique has been recently introduced for the routine, rapid, qualitative detection of the presence hepatitis-B surface antigen (HBsAgl. To evaluate the sensitivity of rapid test, we studied 39 sera positive and one sera negative for HBsAg with conventional ELISA method. The study found that the minimal detectable level of HBsAg with rapid test was 4.03 ng/ml (range 3,25-4,03 ng/ml), it was 8 times less sensitive than conventional ELISA method (4,03 vs 0,47 ng/m1)Ã¢â¬Â¢ Many factors such as